2014
DOI: 10.3390/inorganics2030508
|View full text |Cite
|
Sign up to set email alerts
|

Half-Lantern Pt(II) and Pt(III) Complexes. New Cyclometalated Platinum Derivatives

Abstract: The divalent complex [{Pt(bzq)(μ-L)} 2 ] (1) [Hbzq = benzo[h]quinolone, HL = CF 3 C 4 H 2 N 2 SH: 4-(trifluoromethyl)pyrimidine-2-thiol] was obtained from equimolar amounts of [Pt(bzq)(NCMe) 2 ]ClO 4 and 4-(trifluoromethyl)pyrimidine-2-thiol with an excess of NEt 3. The presence of a low intensity absorption band at 486 nm (CH 2 Cl 2), assignable to a metal-metal-to-ligand charge transfer transition (1 MMLCT) [dσ*(Pt) 2 →π*(bzq)], is indicative of the existence of two platinum centers located in close proximit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…36 Second, dinuclear Pt(III) complexes are believed to be more stable and could accommodate more intimate Pt•••Pt interactions than the dinuclear Pt(II) complexes because of the invulnerability toward nucleophilic reagents (e.g., halide (X − )) for the Pt(III) complexes. 33,37,38 Third, the octahedral coordination geometry allows the attachment of multidentate chelate ligands with various functionalities so that the synergy among the axial coordination ligand, bridging ligand, and cyclometalated ligand can finely harness the Pt•••Pt distance, endowing the corresponding complexes with unique properties. 23,39−41 Despite the fact that many ligands have been employed (e.g., pyridine deriatives, 11,24,33 2-mercaptobenzothiazole and 2mercaptobenzoxazole 25,42,43 ), the endeavors aimed to synthesize emissive dinuclear Pt(III) complexes were not successful.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…36 Second, dinuclear Pt(III) complexes are believed to be more stable and could accommodate more intimate Pt•••Pt interactions than the dinuclear Pt(II) complexes because of the invulnerability toward nucleophilic reagents (e.g., halide (X − )) for the Pt(III) complexes. 33,37,38 Third, the octahedral coordination geometry allows the attachment of multidentate chelate ligands with various functionalities so that the synergy among the axial coordination ligand, bridging ligand, and cyclometalated ligand can finely harness the Pt•••Pt distance, endowing the corresponding complexes with unique properties. 23,39−41 Despite the fact that many ligands have been employed (e.g., pyridine deriatives, 11,24,33 2-mercaptobenzothiazole and 2mercaptobenzoxazole 25,42,43 ), the endeavors aimed to synthesize emissive dinuclear Pt(III) complexes were not successful.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The corresponding stereostructure is beneficial to decreasing quenching by intermolecular interactions such as π-stacking . Second, dinuclear Pt­(III) complexes are believed to be more stable and could accommodate more intimate Pt···Pt interactions than the dinuclear Pt­(II) complexes because of the invulnerability toward nucleophilic reagents (e.g., halide (X – )) for the Pt­(III) complexes. ,, Third, the octahedral coordination geometry allows the attachment of multidentate chelate ligands with various functionalities so that the synergy among the axial coordination ligand, bridging ligand, and cyclometalated ligand can finely harness the Pt···Pt distance, endowing the corresponding complexes with unique properties. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stable Pt III compounds are normally found as oligomers (Pt II –Pt III ) or dimers containing a Pt–Pt bond , and/or bridging ligands. ,, However, stable Pt III mononuclear species are known. , The first mononuclear Pt III complex was reported in 1984 by Usón et al, who synthesized [(NBu 4 )­Pt III (C 6 Cl 5 ) 4 ] by the oxidation of [(NBu 4 ) 2 Pt II (C 6 Cl 5 ) 4 ] with Cl 2 or Br 2 in CCl 4 solution. Later, an EPR study of [(NBu 4 )­Pt III (C 6 Cl 5 ) 4 ] was reported where charge transfer from the ligand to Pt III was proposed.…”
Section: Introductionmentioning
confidence: 99%